1901 N.C. Sess. Laws 160, Pub. Laws, ch. 23, §§ 1, 2. - (:unkn) unknown (General Publisher, 1901)
That it shall be unlawful for any person wantonly, or in sport to shoot or discharge any gun or pistol in, or within two hundred yards or any street in, or any public road leading out of the town of Roper, in the county of Washington, for a distance of one-half mile form the place where the post-office in said town was located on the first day of January, 1901.
--
Keywords: DISCHARGE